MEMBANGUN PROXY SERVER SEBAGAI PENYARING KONTEN DAN MANAJEMEN AKSES JARINGAN INTERNET - Fitri Marisa; Ahmad Irsyadur R (Universitas Merdeka Malang, 2017)
PT.Indomarine a privately omned company engaged in the Manufacture and Boiler Construction, which in activity internet usage there are limitations according to applicable SOP, SOP rules in a regulation of companies to grant access to a particular term, for example, could access the internet only managerial level and above as applied recenty in the environment PT.Indomarine Corp. It is aimed at focus more of its employees to do work and avoid the theft of data from internet access. With such circumstances this system proxy server becomes the best solution for the use of filter. DOI: https://doi.org/10.26905/jtmi.v3i2.1515